Controllers”™ design for the drying rotational oven of the factory “Cementos Cienfuegos S.A.” - Fernández Rodríguez, Ernesto; González Santos, Ana Isabel; íguila CamachoNorelys (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
In this work they intend several strategies for the control of the temperature in a drying rotational oven which is affected by the variations of the flow of matters cousins to the entrance of the drying oven. When varying the flow of matters cousins it varies in a drastic way the temperature inside the drying oven imposing an expense of additional fuel to reestablish the conditions of nominal operation. For the obtaining of the mathematical pattern of the process of variation of temperature in function of the flow of fuel a pseudo random multilevel signal (PRMLS) was used. The results of the simulation of each one of the proposed control strategies, using the pattern of the plant obtained by means of identification, they are compared in function of design specifications, robustness and characteristic of the temporary response.